Extracellular Vesicles: A Potential Novel Regulator of Obesity and Its Associated Complications - Ahlee Kim; Amy S. Shah; Takahisa Nakamura (MDPI AG, 2018)
Childhood obesity continues to be a major public health concern. Obesity causes various metabolic complications, including insulin resistance, type 2 diabetes mellitus (T2DM), non-alcoholic fatty liver disease (NAFLD), dyslipidemia, and cardiovascular disease. However, currently, we have a limited understanding of the pathophysiology in the development of these processes. Extracellular vesicles (EVs) are nano-sized vesicles secreted by different cell types that travel to various organ systems carrying molecular and genetic information. These vesicles have been proposed as a novel intercellular communication mode in systemic metabolic regulation and in several pathophysiologic processes. In particular, recent studies indicate that EVs play a critical role in the pathogenesis of obesity and its metabolic complications. In this study, we reviewed the current literature that supports the role of EVs in the regulation of metabolic homeostasis and pathogenesis of obesity and its associated metabolic complications, with a short discussion about future directions in the EV research field.